Exploring stakeholder perceptions of conservation outcomes from alternative income generating activities in Tanzanian villages adjacent to Eastern Arc Mountain forests. (November 2015) - Sainsbury, K.; Burgess, N.D.; Sabuni, F.; Howe, C.; Puis, E.; Killenga, R.; Milner-Gulland, E.J.
Highlights: "Ranked outcomes" (RO) evaluation method facilitates comparisons between projects. RO is tested using income-generating activity (IGA) projects in Tanzania. RO can be used to capture perspectives of different stakeholders. Tree planting and fish farming were the most socially beneficial IGAs. RO provides important insights in data-poor situations. Abstract: Critical evaluation of the impact of conservation actions is essential to meet the challenges posed by the biodiversity crisis. Conservationists need to understand which interventions work or fail, and how to improve them in order to invest limited funds wisely. Alternative income-generating activities (IGAs) are widely implemented within conservation and development projects, but their impact is rarely evaluated. The "ranked outcomes" evaluation methodology converts qualitative information on planned and realised outcomes into a score for comparison between projects. We test this methodology in two ways using a set of small scale IGAs implemented in communities adjacent to the Uzungwa Scarp proposed Nature Reserve in the Tanzanian Eastern Arc Mountains. The first approach used an independent evaluator and the second assessed project impacts from the perspective of target communities. Both evaluations rated Tree Planting as the most socially beneficial IGA, followed by Fish Farming. However, there was a high level of heterogeneity of perception between and within stakeholder groups (implementers and target communities), both in terms of which outcomes were most important and how well they had been achieved. Ranked outcomes emerged as a flexible framework that defines the terms of the evaluation for all stakeholders from the outset, even in cases when evaluation and clear goal-setting are omitted from original project design and planning. It can be modified for use as a component of rigorous impact assessment, to incorporate perspectives of all stakeholders, and provides important insights in data-poor situations and where baselines are not available.